FY17 Country Opinion Survey Report for Member Countries of the Organisation of Eastern Caribbean States - World Bank Group (World Bank, Washington, DC, 2018)
The Country Opinion Survey in Antigua and Barbuda assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Antigua and Barbuda perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Antigua and Barbuda on 1) their views regarding the general environment in Antigua and Barbuda; 2) their overall attitudes toward the WBG in Antigua and Barbuda; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Antigua and Barbuda; and 4) their perceptions of the WBG’s future role in Antigua and Barbuda.